Entrepreneurial Orientation and Market Innovation: A Conceptual Perspective on Sustainable Competitive Advantage - Hery Margono (International Journal of Science and Society, 2025)
The increasing complexity of the global business environment has intensified competition among organizations, requiring companies to continuously adjust their strategic approaches in order to maintain their market position. Rapid technological developments, shifting consumer preferences, and the expansion of global markets have created new challenges for organizations seeking to sustain long-term competitiveness. In this context, the ability of firms to respond proactively to market dynamics while continuously developing innovative strategies has become increasingly important for ensuring organizational sustainability. This study aims to examine the relationship between entrepreneurial orientation and market innovation in strengthening sustainable competitive advantage from a conceptual perspective. The research employs a qualitative approach through an extensive review of relevant academic literature, including previous studies and scholarly publications related to strategic management, entrepreneurial orientation, and market innovation. The findings indicate that entrepreneurial orientation plays an important role in encouraging organizations to take strategic initiatives and identify emerging market opportunities in dynamic business environments. In addition, the integration of entrepreneurial orientation and market innovation is supported by organizational capabilities such as adaptive structures, effective decision-making processes, coordinated internal functions, and supportive organizational cultures. Ultimately, the development of strategic innovation enables organizations to strengthen sustainable competitive advantage by enhancing their ability to adapt to market changes and maintain stable long-term organizational performance.